Paraoxonase I Activity and Its Relationship with Nutrition in Amyotrophic Lateral Sclerosis - Belén Proaño; María Benlloch; Sandra Sancho-Castillo; Jesús Privado; Guillermo Bargues-Navarro; Claudia Emmanuela Sanchis-Sanchis; Palmira Martínez Bolós; Ana Belén Carriquí-Suárez; Laura Cubero-Plazas; Jose Luis Platero Armero; Dolores Escriva; Jose Joaquín Ceron; et al. (MDPI AG, 2024)
Background: Amyotrophic lateral sclerosis (ALS) is characterized by progressive motor neuron degeneration, with oxidative stress playing a key role. Paraoxonase 1 (PON1) is an antioxidant enzyme that may influence ALS progression. This study aimed to establish a predictive model for the influence of PON1 activity on functionality in ALS patients and explore its relationship with nutrition. Methods: In this observational cross-sectional study, 70 ALS patients underwent assessments of PON1 activity, lipid profile, functional capacity, respiratory function, and heart rate variability. A structural equation model was developed to determine the relationships between variables. Nutritional intake was analyzed in 65 patients. Results: The predictive model showed that PON1 activity and LDL levels positively influenced functionality, both directly and indirectly through respiratory capacity. Heart rate variability moderately predicted functionality independently. HDL levels were not significantly associated with functionality. Weak to moderate correlations were found between PON1 activity and intake of certain nutrients, with positive associations for monounsaturated fats and vitamin D, and negative associations for carbohydrates, proteins, and some micronutrients. Conclusions: PON1 activity appears to play an important role in ALS patient functionality, both directly and through effects on respiratory capacity. However, its relationship with nutritional intake was not strongly evident in this sample population.